Stock price reaction to the announcement of right issues / Hasnida Ismail - Ismail, Hasnida (1995)
Rights issue has been a popular way of financing business by many public- listed corporations. There has been a great deal of finance literature on the effects of this method of financing on stock prices. M any empirical studies conducted earlier shown contradictory results. Some offered a negative effect while others found no price effect. This study examined the effects of stock price on the rights issue announcement in the Malaysian Stock Market. However, methodology being used is the mean adjusted price where the based date is choosen on the 3 month before the announcement Besides that, the study also lend considerable support to the conclusion that the stock market is " efficient " in the sense that the stock prices adjust rapidly to new information. In other words, A s study attempts is to measure the ability of the market to anticipate new information and the speed with which adjust to new information and the purpose of rights issues. The news of the rights issues produces a favourable announcement effect that suggest that companies financing need cause neither surprise nor concern to the market